The taboos of the indigenous people of the Jakun tribe, Kampung Sentosa Lenga, Johor: a preliminary survey - Suhaimi, Mohamad Suhaizi; Mohamad Noor, Mohamad Yusrizal; Abdullah Thani, Nurul Najihah (Human Resource Management Academic Research Society, 2022)
The taboos of the people from the Jakun tribe has formed a unique identity because there are similarities and differences with the Malays. However, research and documentation related to taboos of the Jakun tribe, especially those living in Kampung Sentosa, Lenga, are seen to be less disclosed to the outside community, thus causing a loss in the study of indigenous people. Therefore, this study was conducted to identify and reveal taboos of the Jakun tribe in Kampung Sentosa, Lenga, Johor. This study was conducted using the qualitative method and involved interviews with two informants in an unstructured manner. The selection of the two informants was based on the NORMs approach by Chambers & Trudgill (1990). Research data was collected through interviews, recording, and observation techniques. The findings show that taboos practiced by the Jakun tribe include pregnant women, giving birth, death, engagement, traditional medicine, entering the forest, and marriage. It was found that the taboos are still practiced until now, but there are some practices that are no longer applied due to the lack of awareness of the importance of preserving their culture.